2002
DOI: 10.1080/08958370252809077
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei Induced by Sulfur Dioxide Inhalation in Mouse Bone-Marrow Cells in Vivo

Abstract: Induction effects of sulfur dioxide (SO2) inhalation on micronuclei (MN) formation in the polychromatic erythrocytes (PCE) of mouse bone marrow were studied in vivo. It was shown that SO2 inhalation caused an increase of MN frequencies in the PCE cells in a dose-dependent manner. These results from male and female mice were very similar; no sex difference was observed. These results imply that SO2 is a clastogenic and genotoxic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…SO 2 and its derivatives were previously considered systemic www.nature.com/aps Ma HJ et al Acta Pharmacologica Sinica npg toxic agents that can cause many types of toxic effects, such as chromosomal aberrations, micronuclei, sister-chromatid exchanges [19,[26][27][28][29] , gene mutations [30] , lipid peroxidative damage [31] , DNA damage [32,33] , and changes in some enzyme activities [34] in multiple organs in mice and rats. Studies have also indicated that SO 2 inhalation can also cause gene expression changes and alter cytokine levels in the rat lung [35] .…”
Section: Discussionmentioning
confidence: 99%
“…SO 2 and its derivatives were previously considered systemic www.nature.com/aps Ma HJ et al Acta Pharmacologica Sinica npg toxic agents that can cause many types of toxic effects, such as chromosomal aberrations, micronuclei, sister-chromatid exchanges [19,[26][27][28][29] , gene mutations [30] , lipid peroxidative damage [31] , DNA damage [32,33] , and changes in some enzyme activities [34] in multiple organs in mice and rats. Studies have also indicated that SO 2 inhalation can also cause gene expression changes and alter cytokine levels in the rat lung [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Though according to the International Agency for Research on Cancer SO 2 is not classifiable as to its carcinogenicity (IARC, 1992), some studies have associated this gas with DNA damage. Meng et al (2002Meng et al ( , 2005 have reported that inhaled SO 2 damaged the DNA of multiple organs of mice (in addition to the lung) and suggested that the damages could result in mutation, cancer, and other diseases related to DNA damage. Some studies have shown that occupational exposure to SO 2 increases DNA damage in peripheral blood lymphocytes of workers (Yadav and Kaushik, 1996), and epidemiological evidence has linked SO 2 exposure with lung cancer (Lee et al, 2002;Pope et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies Meng et al (2002) investigated the induction of micronuclei in bone marrow cells of male and female Kunming mice following inhalation exposure to sulfur dioxide. Concentrations of 0, 14, 28, 56 and 84 mg SO 2 /m 3 were administered to groups of five male and five female mice for 4h/day for 7 days.…”
Section: Sulfur Dioxidementioning
confidence: 99%